Sharia Enterprise Theory: Integration of The Concept of Trust in The Amil Zakat Institution - Ahmad Zikri Dwiatmaja; Muhammad Danial Tompson; Saiful Muchlis (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
Purpose - Zakat is one of the pillars of Islam that is very important, functioning as the main instrument in realizing trust and improving the welfare of the people. In order for the noble goal of zakat to be achieved, zakat management needs to be carried out in a professional and good way (good zakat governance), which means that zakat must be managed systematically in accordance with Islamic sharia principles. The management of zakat must include aspects of trust, utility, justice, legal certainty, integration, and accountability. Method - This research uses a qualitative approach with a literature study that examines various sources related to Sharia Enterprise Theory integrated with the concept of trust and its application in amil zakat institutions. Result - The results of the study show that the application of this theory is in accordance with the role of humans as khalifatullah fil ardh, who is tasked with creating and distributing welfare for humanity and nature. Thus, Sharia Enterprise Theory is a development of Enterprise Theory that has been integrated with Islamic values, resulting in a more transcendental and humanist theory. In the perspective of Sharia Enterprise Theory, stakeholders consist of God, humans, and nature, with God as the supreme party that is the goal of human life. Humans as caliphs on earth have a mission to create and distribute prosperity for all creatures and the universe. The problem that still exists is that there are still many people who do not fully understand the importance of trust in managing zakat. Sometimes, zakat amil institutions feel pressured to achieve high zakat collection targets, thereby ignoring the principles of trust. Implication - Implementing the trust concept is an ongoing process. It requires a strong commitment from all parties involved to realize better and more beneficial zakat management for the community.